Enhancing Children’s English Learning Motivation through Fun Learning with a Foreign Speaker at Gunung Mas Village - Khodijah, Fadila Umi; Norahmi, Maida; Farid, Rezqan Noor; Almuntaser, Majd; Valindra, Rayya Izzati (Jurnal Pengabdian Masyarakat Bhinneka, 2025)
This community service program aimed to enhance children’s motivation to learn English in Gunung Mas Village through the implementation of a fun learning approach involving a foreign speaker. The approach emphasizes enjoyment, active engagement, and hands-on experience as the core of the learning process. The “Kelas Pelita” program consisted of three interactive sessions focusing on the topics of the alphabet, numbers, colors, fruits and body parts, integrating four main elements: Game-Based Learning (GBL), Communicative Language Teaching (CLT), Total Physical Response (TPR), and the use of digital media. The results showed that students became more enthusiastic, confident, and willing to communicate in English. Direct interaction with a foreign speaker from Yemen provided authentic language exposure and increased students’ curiosity toward English as a global communication tool. Through the fun learning approach, this activity successfully created a positive, interactive, and meaningful learning atmosphere for children in a rural area.